Organization Development: a data- driven approach to organizational change - Waclawski, Janine; Church, Allan H. editor 1966- (The professional practice series, 2002)
This hands-on guide--for planning, diagnosing, implementing, and evaluating organization development interventions--gives scientifically based information, tools, suggestions, and guidelines for those who must manage the human side of change.